Computers in Fisheries Research - Megrey, Bernard A.; Moksness, Erlend (Springer Netherlands : Imprint: Springer, 2009)
This is the second edition of a book that reviews current and future computer trends in fisheries science applications. The first edition was published 10 years ago. Individuals have been quick to realize the potential of computers in fisheries and scientists continue to take advantage of the rapidly advancing tools and technology. This book provides a valuable sampling of contemporary applications and in some cases compares recent developments to the status of the situation 10 years ago. In many cases perspectives are presented by the same authors that contributed to the first edition. Scientists will have an opportunity to evaluate the suitability of different computer technology applications to their particular research situation thereby taking advantage of the experience of others.